Teologi Hospitalitas: Sebuah Diskursus Konstruktif Agama Merevitalisasi Nilai-nilai Kemanusiaan - Siahaan, Harls Evan R; Kause, Munatar; Siagian, Fereddy (KAMBOTI: Jurnal Sosial dan Humaniora, 2022)
The sense of humanity has been disrupted by issues that have led to conflict and violence in the name of religion. Religious identity is often used as a barrier that sharply distinguishes adherents of one religion from another so that the identity differences put each as "strangers". Christianity strives to reflect and at the same time answer the challenges of the social and humanities crisis through theological discourses, both in academic and pastoral contexts. This article aims to offer a theological construction that reflects the law of love as a means of revitalizing human values. This qualitative approach using descriptive analysis methods from various literature resulted in a discourse on the theology of hospitality which embodies the law of love for others as an attitude of Christian hospitality in doing religion in a togetherness space. In conclusion, the theology of hospitality can be one of the doctrines to revitalize human values in doing religion from a Christian perspective.